Sistem Informasi Geografis (SIG) Properti di Kota Tanjungpinang Berbasis Website - Dwi Nurul Huda; Angger Andrea Amanda; Dedy Jauhari (Jurnal Bangkit Indonesia, 2019)
The increasing need for property in Tanjungpinang City is very growing, especially in the housing sector. Selection of property based on location and facilities and infrastructure is always a consideration for the community in making decisions to buy a property. Difficulty finding property location information in a certain area often occurs, resulting in people not getting references about the properties offered in Tanjungpinang City. The purpose of this research is to create a web-based geographic information system (GIS) regarding the distribution of the number of properties on offer, especially in Tanjungpinang City using a web-based mapping approach. In the development of Property GIS the author uses the Waterfall method and in the analysis of system requirements it is modeled with UML (Unified Modeling Language) and implemented with the PHP programming language and MySQLI database. It is hoped that the results of making this property's geographic information system can help the public to find out information about the distribution of properties offered, such as the location of property coordinates, addresses, prices, property photos, property specification data and property developer data.